Milei’s extremist ArgentinaA Argentina extremista de Milei - Beltrán-Conejo, Vanesa (2025)
In 2023, Javier Milei rose to power in Argentina. In a regional and globalcontext marked by the delegitimization of democratic systems, a lack ofcredibility in traditional political parties, political and economic corruption,and the emergence of disruptive figures such as Bukele in El Salvador andBolsonaro in Brazil, Latin America is witnessing a kind of anti-democraticpolitical undertow. The content provided below analyzes the current situationin Argentina under Milei’s government. Political scientist Vanesa BeltránConejo addresses the main political, economic, and social challenges facingthe country. She reviews the measures taken by the Argentine government,their impact on people’s daily lives, and how this could affect the country’sdemocracy in the short and medium term.